Properties of Some Dynamic Partial Integrodifferential Equations on Time Scales - Pachpatte, Deepak B. (Communications in Mathematics and Applications, 2018)
The main objective of this paper is to study some properties of new dynamic equations partial integrodifferential equations in two independent variables on time scales. The tools used in obtaining our results are application of Banach Fixed point theorem. We also used dynamic inequality with explicit estimates to study the properties of solution of dynamic partial integrodifferential equation.